2017
DOI: 10.1371/journal.pone.0187801
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hospitalized elderly patients at risk for adverse in-hospital outcomes in a university orthopedics and trauma surgery environment

Abstract: BackgroundAs a consequence of demographic changes, hospitals are confronted with increasing numbers of elderly patients, who are at high risk of adverse events during hospitalization. Geriatric risk screening followed by comprehensive geriatric assessment (CGA) and treatment has been requested by geriatric societies and task forces to identify patients at risk. Since empirical evidence on factors predisposing to adverse hospital events is scarce, we now prospectively evaluated implications of geriatric risk sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 41 publications
0
29
0
3
Order By: Relevance
“…Specifically, trauma patients experience increased incidence of mood disorders, psychotic disorders and anxiety disorders that often last beyond the acute phase of physical recovery . It is also well documented that mental health outcomes such as depression and PTSD contribute to negative outcomes of trauma patients such as increased hospital length of stay , increased healthcare utilization and increased medical symptoms and complications . Further, depression and symptoms of post‐traumatic stress among trauma patients in the first year following injury are significantly higher compared to the general population, with an estimated prevalence ranging from 28% to 42% .…”
mentioning
confidence: 99%
“…Specifically, trauma patients experience increased incidence of mood disorders, psychotic disorders and anxiety disorders that often last beyond the acute phase of physical recovery . It is also well documented that mental health outcomes such as depression and PTSD contribute to negative outcomes of trauma patients such as increased hospital length of stay , increased healthcare utilization and increased medical symptoms and complications . Further, depression and symptoms of post‐traumatic stress among trauma patients in the first year following injury are significantly higher compared to the general population, with an estimated prevalence ranging from 28% to 42% .…”
mentioning
confidence: 99%
“…Since the number of such patients at risk is expected to increase due to demographical changes, attempts have been made to identify these patients using screenings and assessments [9,10]. By now the ISAR screening tool is one of the most commonly used tools to predict the risk of functional decline in older patients [6,11,12]. For high-risk patients with positive ISAR screening a comprehensive geriatric assessment (CGA) is recommended as a second diagnostic step.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Sousa et al found that nursing hours in intensive care patients were predicted by higher age and severity of illness and it were higher in surgical patients than in patients in internal medicine wards [21]. In patients admitted to surgery wards, comorbidities, the ISAR score, mobility impairment, ADL impairment and cognition impairment were predictors of nursing hours [6]. Evidence for the prediction of nursing hours in internal medicine in-patients is still missing as is evidence for the prediction of physiotherapy, which reflects mobility impairment and also contributes to functional recovery, in internal medicine inpatients.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, the proportion of people 65 years and older increased from 16.6% in 2005 to 18.9% in 2015, with Germany, Italy and Greece having the highest share of people 65 years and older in the total population. The median age of the total population also increased by about 4 years from 2005 to 2015 so that the proportion of older people will increase strongly in the future.…”
mentioning
confidence: 99%
“…We for the first time evaluated ISAR screening followed by standardized comprehensive geriatric assessment in a German university orthopedics and trauma surgery environment [16]. ISAR consists of 6 questions with dichotomized yes/no answers assessing functional dependence (premorbid and acute change), recent hospitalization, impaired memory and impaired vision and polymedication (≥ 6 medications) [12].…”
mentioning
confidence: 99%